Prognostic impact of lipoprotein(a) levels during lipid management with statins after ST-elevation acute myocardial infarction. Issue 8 (December 2019) - Mitsuda, Takayuki; Uemura, Yusuke; Ishii, Hideki; Tanaka, Akihito; Takemoto, Kenji; Koyasu, Masayoshi; Ishikawa, Shinji; Shibata, Rei; Watarai, Masato; Murohara, Toyoaki
Abstract : The causal relationship of lipoprotein(a) with cardiovascular disease has been established. However, clinical impacts of lipoprotein(a) levels on adverse vascular events in patients with established coronary artery disease who are undergoing statin treatment have not been fully elucidated. We measured lipoprotein(a) levels of 668 consecutive patients with ST-elevated myocardial infarction upon admission and reevaluated lipoprotein(a) of 189 of these patients during statin treatment at least 6 months later than the date of index ST-elevated myocardial infarction. Changes in lipoprotein(a) and associations between lipoprotein(a) levels and the incidence of major adverse cardiac and cerebrovascular event for 3 years were examined. Lipoprotein(a) at baseline was an independent predictor of 3-year major adverse cardiac and cerebrovascular event after ST-elevated myocardial infarction. Levels of lipoprotein(a) at follow-up were slightly but significantly elevated despite improvements in other lipid parameters due to statin treatment. Furthermore, higher levels of lipoprotein(a) achieved with statin treatment were also associated with the subsequent incidence of major adverse cardiac and cerebrovascular event over 3 years, regardless of whether or not the LDL-cholesterol levels were below 100 mg/dl. In conclusion, lipoprotein(a) levels during lipid management by statin are also predictive of adverse vascular events in Japanese patients with ST-elevated myocardial infarction.